Pengaruh Kecerdasan Spiritual, Emosional, Intelektual, dan Sosial terhadap Sikap Etis Mahasiswa se-Pulau Lombok - Lalu Takdir Jumaidi; Bambang Bambang; Iman Waskito (Sekolah Tinggi Ilmu Ekonomi AMM, 2022)
Abstract Initiating from the increasing moral hazard occurred, this study aims to examine the effect of spiritual, emotional, intellectual and social intelligence on the ethical attitudes of accounting students. Approach used is quantitative, data analysis used SPSS. The results showed that spiritual and emisional intelligence showed the positive significant influence on ethical behavior of students. Spritual intelegence showed highest level, next is emotional intelligence. This condition shows that spiritual and emotional intelligence have a very strategic position, which can be used as